Venture Sendirian Berhad : The Journey to Excellence - Quoquab, Farzana; Mahadi, Nomahaza; Wan Abdullah, Taram Satiraksa; Mohammad, Jihad (2017)
Venture Sendirian Berhad (subsequently known as Venture) was an oil and gas company which was in charge of handling the small and marginal fields that had smaller reservoir in Malaysia.The company was comparatively new. In the middle of 2014, the company encountered an accident while handling one of the projects.The fire was caught in the pump room which caused almost RM 21 million of losses.After investigating the situation, it was revealed that the main reason for this incidence was people's negligence.Considering the seriousness of the issue, Mr Alvin James, The CEO of Venture suggested Mr Abid Rashid the head of Health and Safety department of Venture to bring the pro-active safety culture among the employees on or before December, 2015. Mr Alvin was afraid, if the employees were not alert and aware of the safety culture, such incidence might occur again and again.